Langmuir Probe Method for Precise Evaluation of the Negative‐Ion Density in Electronegative Gas Discharge Magnetized Plasma. Issue 1 (9th January 2013) - Popov, Tsv. K.; Mitov, M.; Bankova, A.; Ivanova, P.; Dimitrova, M.; Rupnik, S.; Kovačič, J.; Gyergyek, T.; Cerček, M.; Dias, F. M.
Abstract The paper reports results from Langmuir probe current‐voltage (IV) characteristic measurements in argon and oxygen low‐gas‐pressure magnetized plasma. The plasma was produced in a stainless steel discharge tube with length 1.5 m and diameter 0.17 m with a hot filaments cathode. The wall of the discharge tube was grounded. An axial magnetic field B was created by a solenoid. A platinum cylindrical Langmuir probe with radius R = 5· 10−5 m and length L = 5· 10−3 m was placed axially and radially at the center of the discharge tube in order to perform measurements along and across the magnetic field. Using the second derivatives of the measured IV probe characteristics, the EEDF in argon and oxygen was evaluated. The derivatives were taken numerically. Measurements in an argon (i.e., in the absence of negative ions) were performed to obtain results for comparison with the measurements in an oxygen gas discharge, where a high density of negative ions is expected. In the measurements of the second derivatives of the IV characteristics with the probe parallel to the magnetic field in oxygen, a peak appears close to the plasma potential due to the registration of negative ions. In the same time, the electron part of the second derivative was substantially suppressed relatively to the case with the probe oriented perpendicular to the magnetic field. Thus using the appropriate orientation of the probe and a low magnetic field, when the electron part of the second derivative is suppressed, since the negative ion part is not affected by the low magnetic field applied, we can evaluate precisely the negative ion density. The results from the plasma parameters evaluation (plasma potential, electron and negative ion densities and electron temperatures) are presented and discussed (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)